2008
DOI: 10.1158/0008-5472.can-08-2428
|View full text |Cite
|
Sign up to set email alerts
|

Atu027, a Liposomal Small Interfering RNA Formulation Targeting Protein Kinase N3, Inhibits Cancer Progression

Abstract: We have previously described a small interfering RNA (siRNA) delivery system (AtuPLEX) for RNA interference (RNAi) in the vasculature of mice. Here we report preclinical data for Atu027, a siRNA-lipoplex directed against protein kinase N3 (PKN3), currently under development for the treatment of advanced solid cancer. In vitro studies revealed that Atu027-mediated inhibition of PKN3 function in primary endothelial cells impaired tube formation on extracellular matrix and cell migration, but is not essential for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
175
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(184 citation statements)
references
References 48 publications
5
175
0
1
Order By: Relevance
“…With respect to immunoliposomes, although many preclinical studies can be found in the literature [24,215,275,276] and a few clinical trials are in progress [18,75,[277][278][279] an siRNA that targets PKN3 [18,286], or TKM-PLK1 that includes siRNA against PLK1 for the treatment of neuroendocrine tumors and adrenocortical carcinomas (phase I/II clinical trials) [283,287,288]. The phase I liposomic formulation SGT-53 includes plasmidic DNA that expresses the tumor suppressor gene p53 to treat solid tumors [280,289].…”
Section: Nl Cpt-11mentioning
confidence: 99%
“…With respect to immunoliposomes, although many preclinical studies can be found in the literature [24,215,275,276] and a few clinical trials are in progress [18,75,[277][278][279] an siRNA that targets PKN3 [18,286], or TKM-PLK1 that includes siRNA against PLK1 for the treatment of neuroendocrine tumors and adrenocortical carcinomas (phase I/II clinical trials) [283,287,288]. The phase I liposomic formulation SGT-53 includes plasmidic DNA that expresses the tumor suppressor gene p53 to treat solid tumors [280,289].…”
Section: Nl Cpt-11mentioning
confidence: 99%
“…However, delivering siRNA to tumors using clinically acceptable delivery strategies remains a major technical hurdle (2,3). Over the last 10 years, various proof-of-concept successes of in vivo siRNA delivery to tumors have been reported using delivery vehicles such as liposomes, cationic polymers, and other materials (4)(5)(6)(7)(8)(9)(10). To select the most promising delivery platform for the development of siRNA therapeutics, we evaluated the majority of available delivery technologies for their abilities to deliver siRNA into tumors using the previously described positive-readout tumor models (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, siRNA administered through this route can be easily degraded. 19 In many cases, siRNA induces the silencing of unintended genes (off-target effects) because of sequence similarity between the mRNAs of the target and nontarget genes. 20 Furthermore, siRNA readily induces immune responses in vivo.…”
Section: Discussionmentioning
confidence: 99%